Development and biological characterization of an infectious cDNA clone of NADC34-like PRRSV - Lin, Yafang; Zhou, Lujia; Xiao, Changguang; Li, Zongjie; Liu, Ke; Li, Beibei; Shao, Donghua; Qiu, Yafeng; Ma, Zhiyong; Wei, Jianchao (Frontiers in Microbiology, 2024)
Porcine Reproductive and Respiratory Syndrome virus (PRRSV) causes high abortion rates in gestating sows and stillbirths, as well as high piglet mortality, seriously jeopardizing the pig industry in China and worldwide. In this study, an infectious clone containing the full-length genome of NADC34-like PRRSV was constructed for the first time using reverse genetic techniques. The gene was amplified segmentally onto a plasmid, transfected into BHK-21 cells, and the transfected supernatant was harvested and transfected into PAM cells, which showed classical cytopathic effects (CPE). The virus rJS-KS/2021 was successfully rescued which could be demonstrated by Western Blot and indirect immunofluorescence assays. Its growth curve was similar to the original strain. Replace the 5'UTR and 3'UTR of rJS-KS/2021 with 5'UTR and 3'UTR of HP-PRRSV (strain SH1) also failed to propagate on MARC-145. These findings provide a solid foundation for studying the recombination of different PRRSVs and the adaption of PRRSVs on MARC-145 in the future.